2010
DOI: 10.1063/1.3385433
|View full text |Cite
|
Sign up to set email alerts
|

Impulse and particle dislodgement under turbulent flow conditions

Abstract: In this study, we investigated the role of turbulence fluctuations on the entrainment of a fully exposed grain near threshold flow conditions. Experiments were carried out to measure synchronously the near bed flow velocity and the particle movement for a range of flow conditions and resulting particle entrainment frequencies. We used a simplified bed geometry consisted of spherical particles to reduce the complexities associated with the variations in the bed and flow details in an effort to identify the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(153 citation statements)
references
References 33 publications
7
136
0
Order By: Relevance
“…For more details, see Celik et al [2010]. The sampling duration for each flow condition in all experiments was 15 min with an average data rate of 250 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For more details, see Celik et al [2010]. The sampling duration for each flow condition in all experiments was 15 min with an average data rate of 250 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…By nondimensionalizing the random impulse variable, I, with its ensemble average value, I mean , asÎ ¼ I=I mean , Celik et al [2010] determined that the following log-normal expression represents the corresponding probability density function (pdf) well,…”
Section: Distribution Of Directly Detected Impulse Events With F D ! mentioning
confidence: 99%
See 2 more Smart Citations
“…The pioneering studies by Einstein 31 (1950), Sutherland (1967) and Grass (1970) have contributed to the development of modeling 32 approaches that described particle entrainment using probabilistic concepts (e.g., Cheng Recently, two additional aspects were experimentally investigated that characterize physical 36 interactions at the sediment-flow interface. First, it was clarified that the duration of the 37 hydrodynamic forces, not only their magnitude, is important in determining whether a grain will be 38 entrained, thus arguing that a threshold criterion would be better described by an impulse rather 39 than a force balance (Diplas et al 2008;Celik et al 2010; Valyrakis et al 2010). Second, while most 40 past investigations have assumed turbulent flow and bed particle arrangement to be statistically 41 independent, evidence was found that they have dependence (Papanicolaou et al 2001; Dey et al 42 2011a; Tregnaghi et al 2012a).…”
Section: Introduction 24mentioning
confidence: 99%